Flame investigations of a laboratory-scale CECOST swirl burner at atmospheric pressure conditions. (1st November 2020) - Subash, Arman Ahamed; Yu, Senbin; Liu, Xin; Bertsch, Michael; Szasz, Robert-Zoltan; Li, Zhongshan; Bai, Xue-Song; Aldén, Marcus; Lörstad, Daniel
Abstract: Experimental and numerical studies were performed to understand the stabilization of lean premixed natural gas/air flames in a gas turbine model combustor which was equipped with a swirl burner, known as the CECOST burner, designed to replicate the flow and flame structures in an industrial gas turbine engine. The operability range, flame stabilization, and flashback were investigated employing simultaneous OH– and CH2 O-PLIF, and high-speed chemiluminescence imaging. Large eddy simulation (LES) was carried out for analysis of the vortex breakdown structures under non-reacting conditions. It was found that the vortex breakdown structures under isothermal conditions were insensitive to the Reynolds number (Re) for Re ≥ 10000; however, the stability of the flames and operability range of the burner were highly sensitive to Re as well as to equivalence ratio (ϕ). The equivalence ratio was varied at various Reynolds numbers to observe different regimes of the flame ranging from the lean blowout (LBO) limit to the flashback limit. The LBO limit was found to be mainly a function of equivalence ratio while being nearly independent of the Reynolds number, whereas the occurrence of flashback showed distinct characteristics for different ranges of the Reynolds number. At low and moderate Reynolds numbers, (Re ≤ 17000), flashback occurred when increasing ϕ from lean towards stoichiometric conditions. The coupling between the flow field and heat release induces vortex breakdown in the mixing tube and initiates flashback. In contrast, at higher Reynolds numbers (Re > 17000) no flashback was observed even when ϕ was increased to stoichiometric conditions. At these conditions with high Re, the increase in the bulk flow velocity affects the vortex breakdown structure, pushing the vortex breakdown downstream, which in turn prevents the flame from flashing back into the mixing tube.